The Impact of the Crusader Attacks on Extending Zanki Influence over Egypt (559-567 AH / 1164-1172 AD)))) - Mohammed Abbas, Jasim (Journal of College of Education, 2021)
The research sheds light on an important period in the history of Egypt during the Fatimid rule (358-567 AH / 969-1172) and examines the impact of the Crusader attacks on the extension of Zanki influence over Egypt, and the significant political events that resulted from them in the history of this country. It has a clear change in its political map. In time; The Crusader forces were waiting for opportunities to launch attacks on Egypt, King Noureddine Zangi watched those attacks closely, so he proceeded to send his military campaigns to them to secure their borders from possible crusader attacks, as well as his pursuit of his goal that represented his control over Egypt, ending the Fatimid rule, and returning it to the fold of the Abbasid Caliphate in Baghdad through the publication of the doctrines of the Sunnis and the Jamaa, and the responsibility for implementing this was assigned to the leader of his military campaigns, Asad al-Din Shirkuh and his nephew Salah al-Din al-Ayyubi, and this was achieved for him. These leaders succeeded in extending the influence of the Zangid over Egypt, after the name of the Fatimid Caliph Al-Aded was removed from the Friday sermon in the year 567 AH / 1172 and the sermon of the Abbasid caliph in Baghdad instead. According to the significance of these political events, we chose the research project that came under the title (The Impact of the Crusader Attacks on Extending the Zangid Influence on Egypt 559-567 AH / 1163-1172 AD) and touched upon the discussion of the three military campaigns; Which was sent by King Nur al-Din Zangi to Egypt - to secure it from the Crusader attacks - and it had the most prominent effect on extending the Zangid influence over it.